2017
DOI: 10.22214/ijraset.2017.4076
|View full text |Cite
|
Sign up to set email alerts
|

Network Connectivity Optimization for Device-to-Device Wireless System with Femto Cells

Abstract: The demand for high data rate transmission has triggered the design and development of advanced cellular networks, such as 4th generation long term evolution (LTE) networks. However, their poor coverage and relatively high interference can significantly impair data transmission. Femtocell and device-to-device (D2D) communication are promising solutions that have recently gathered interest. Operating in the licensed spectrum, femtocells provide users with higher capacity and coverage than their earlier designs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The several challenges in developing scalable and defect-free transition metal dichalcogenides on desired substrates, new growth techniques compatible with traditional and unconventional substrates have been developed to meet the ever-increasing demand of high quality and controllability for practical applications [19]. The proposed method is to reduce the thermal discomfort by using phase change material (PCM) to absorb and to store the excessive heat produced by the solar radiation to attain the comfort cooling for the wearer [20]. The aforementioned literature revealed that the unique properties of graphene and TCM material based phase change material is need an attention for future energy application.…”
Section: Introductionmentioning
confidence: 99%
“…The several challenges in developing scalable and defect-free transition metal dichalcogenides on desired substrates, new growth techniques compatible with traditional and unconventional substrates have been developed to meet the ever-increasing demand of high quality and controllability for practical applications [19]. The proposed method is to reduce the thermal discomfort by using phase change material (PCM) to absorb and to store the excessive heat produced by the solar radiation to attain the comfort cooling for the wearer [20]. The aforementioned literature revealed that the unique properties of graphene and TCM material based phase change material is need an attention for future energy application.…”
Section: Introductionmentioning
confidence: 99%